1964. Microbiological Outcomes With Plazomicin (PLZ) vs. Colistin (CST) in Patients With Bloodstream Infections (BSI) Caused by Carbapenem-Resistant Enterobacteriaceae (CRE) in the CARE Study. (26th November 2018) - Serio, Alisa W; Smith, Alex; Krause, Kevin M; Galani, Irene; Gales, Ana Cristina; Jubb, Adrian; Connolly, Lynn E
Abstract: Background: PLZ is a next-generation aminoglycoside with structural modifications that protect it from aminoglycoside-modifying enzymes (AMEs) and in vitro activity against multidrug-resistant (MDR) Enterobacteriaceae, including aminoglycoside- and carbapenem-resistant strains. In the CARE study, PLZ was associated with improvement in 28-day all-cause mortality vs. CST in patients with CRE BSI. We report the microbiological outcomes in the CARE study by pathogen and key resistance mechanism. Methods: CARE was a multinational, open-label trial that enrolled BSI patients with documented or presumed CRE into two cohorts. Patients in the randomized cohort received PLZ (15 mg/kg q24h IV) or CST (300-mg load [CST base activity] then 5 mg/kg/day IV) plus adjunctive tigecycline or meropenem. Patients in the observational cohort received PLZ plus investigator's choice of adjunctive agent. Treatment duration was 7–14 days. Isolate identification and susceptibility testing were conducted by a central laboratory. Whole-genome sequencing was used to identify AME and carbapenemase genes. Microbiological outcomes were assessed in patients with confirmed CRE who received ≥1 dose of study drug (mMITT population). Results: Of 45 BSI patients enrolled, 43 had confirmed CRE (mMITT), including Klebsiella pneumoniae ( n = 42) and Enterobacter aerogenes ( n = 1). Against CRE, PLZ MICs ranged from 0.12 to >128 µg/mL; 25/28 (89.3%) isolates from PLZ-treated patients had a PLZ MIC ≤4 µg/mL, while 3 had a PLZ MIC ≥128 µg/mL and a confirmed 16S ribosomal methyltransferase gene. CST MICs ranged from 0.25 to >128 µg/mL; 6/16 (37.5%) isolates from CST-treated patients had an MIC >2 µg/mL. There were 47 distinct Enterobacteriaceae pathogens isolated from 43 patients, and of these, AME genes were detected in 43/47 (91.5%), most commonly aac(6')-Ib (n = 29). Carbapenemase genes were detected in 45/47 (95.7%) isolates, most commonly bla KPC ( n = 33). PLZ demonstrated higher microbiological eradication rates than CST against CRE, including AME- and carbapenemase-producing isolates (table). Conclusion: The results provide evidence of the efficacy of PLZ-based therapy for patients with BSI due to MDR Enterobacteriaceae, including AME- and carbapenemase-producing organisms. Disclosures: A. W. Serio, Achaogen, Inc.: Employee and Shareholder, Salary. A. Smith, Achaogen, Inc.: Employee and Shareholder, Salary. K. M. Krause, Achaogen, Inc.: Employee, Salary. I. Galani, Achaogen, Inc.: Scientific Advisor, Research funding and honoraria. MSD: Scientific Advisor, Honoraria. A. C. Gales, MSD: Consultant and Speaker, Consulting fee. Pfizer: Consultant and Speaker, Consulting fee. BD: Consultant, Consulting fee. Bayer: Consultant, Consulting fee. A. Jubb, Achaogen, Inc.: Employee and Shareholder, Salary. L. E. Connolly, Achaogen, Inc.: Consultant, Consulting fee.